Comparison of the Flow Behaviours of Physical and Numerical Models on a Stepped Spillway - Kuljitjuawong, Treerat; Kositgittiwong, Duangrudee; Ekkawatpanit, Chaiwat; Sukjan, Rachapol (Applied Science and Engineering Progress, 2021)
A massive water release can create high discharge and high velocity, which in turn can lead to erosion at the surface of a spillway. The difficulties of data collection and the high cost of experiments impose barriers to the study of large spillways. A numerical model that can simulate the flow behaviour is a valid choice to solve this problem. The objective of this research is to study the flow behaviour and flow velocity triggered by physical model tests and numerical model simulations. The small differences between the results of the two models illustrate that the numerical model is reliable and can be used to design a stepped spillway. Computational fluid dynamics (CFD) is a numerical modelling technique used in this study. For the numerical modelling of turbulence, the k–epsilon turbulence model is used. This model comprises 3 submodels: The standard k–epsilon, renormalized group (RNG) k–epsilon and realizable k–epsilon models. The results show that the RNG k–epsilon model is the most suitable model. The results reveal that the stepped spillway results in a 98% reduction of energy dissipation based on the present case study. The quantified differences between the results of the physical model and those of the numerical model are approximately 0.1–11.23%.